Analisis Manfaat Implementasi SIMRS Webview di Instalasi Radiologi RSUD Dr. R. Soetijono Blora - Edelweis Kusumawardhani Jatmiko; Anshor Nughroho; Tris Budiyono (Pusat Riset dan Inovasi Nasional, 2025)
The Hospital Management Information System (SIMRS) is an essential instrument in supporting data management and enhancing healthcare services more effectively. This system is designed to provide accurate, fast, and reliable information, thereby facilitating decision-making processes within hospital environments. The Radiology Department of Dr. R. Soetijono Regional General Hospital, Blora, has adopted a WebView-based SIMRS as part of its digital transformation efforts. The procedure begins with patient data management initiated by referring physicians. The data are then imported into the SIMRS, which is automatically connected to the radiology department, thereby simplifying the workflow of patient examination services. The objective of this study is to evaluate the benefits and effectiveness of using SIMRS Pilar compared to SIMRS WebView, particularly in the context of radiology services. This research employed a quantitative method using a questionnaire consisting of 30 items, which was distributed to 13 radiographers directly involved in service delivery through SIMRS. The findings indicate that SIMRS WebView significantly improves service efficiency. This is reflected in faster patient data entry and access, smoother integration between hospital units, and a reduction in errors and data redundancy. Validity testing of the research instrument showed that all items had correlation values above 0.444 with significance levels below 0.50, confirming their validity. In addition, respondents considered the new system more practical compared to the previous one, as it allows access through devices connected to the hospital’s internal network. Nevertheless, the study also identified several technical challenges, such as unstable network connectivity and the need for adaptation among users who were not yet fully familiar with web-based technology. Overall, the study concludes that the implementation of SIMRS WebView in the Radiology Department of Dr. R. Soetijono Regional General Hospital is effective and beneficial in improving service quality.